Millennial dawn - Russell, C. T. (Helping hand for Bible students, 1891)
v. 1. The plan of the ages.--v. 2. The time is at hand.--v. 3. Thy kingdom come.--v. 4. The day of vengeance.--v. 5. The at-one-ment between God and man.